2008
DOI: 10.1080/13854040701281483
|View full text |Cite
|
Sign up to set email alerts
|

Automated Neuropsychological Assessment Metrics (Anam) and Woodcock-Johnson III Tests of Cognitive Ability: A Concurrent Validity Study

Abstract: This study examines the relationship between a computerized neuropsychological assessment battery, the Automated Neuropsychological Assessment Metrics (ANAM) and a widely used ability measure, Woodcock-Johnson III Tests of Cognitive Ability (WJ-III). Results indicated substantial relationship between the ANAM throughput (accuracy/response time) scores and the WJ-III Cognitive Efficiency cluster. An unexpectedly strong relationship was evident between accuracy scores on the ANAM Logical Reasoning scale and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Low Ped‐ANAM TP scores have been reported in numerous clinical populations as demonstration of cognitive difficulties (8, 15, 32–35). However, we did not find the TP scores to be useful in differentiating study participants according to the level of their cognitive function, which is most likely due to atypical performance patterns that led to this variable being an overestimate of actual cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Low Ped‐ANAM TP scores have been reported in numerous clinical populations as demonstration of cognitive difficulties (8, 15, 32–35). However, we did not find the TP scores to be useful in differentiating study participants according to the level of their cognitive function, which is most likely due to atypical performance patterns that led to this variable being an overestimate of actual cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
“…69 Those with previously unidentified TBI reported slightly more (rather than less) mood and physical symptoms, but the difference was not significant. Individuals in both groups performed similarly on the Automated Neuropsychological Assessment Metrics (ANAM 4) 70 computerized assessments of processing speed, attention, encoding, spatial processing, and accuracy ( P values ranged from 0.20 to 0.95), but individuals with unidentified TBI demonstrated poorer working memory ( P = 0.049). These findings indicate that, while individuals in the community with previously unidentified TBI have similar symptom profiles as individuals with known TBI and in some areas may demonstrate poorer functioning, they do not causally associate their symptoms with a prior brain injury.…”
Section: Estimating Prevalence Of Tbi In Community Samplesmentioning
confidence: 99%
“…Several studies have addressed examining the validity of ANAM subtests with conventional paper-and-pencil tests. [18][19][20] Overall findings demonstrated that ANAM is capable of assessing cognitive constructs similar to their conventional neuropsychological counterparts in the areas of working memory, processing speed, and cognitive efficiency. Test-retest reliability on the sports version of ANAM yielded moderate correlation coefficients on almost all measures (r ranging from 0.38 to 0.66), except for the mathematical processing test that showed the highest reliability value (r ¼ 0.87) when testing athletes on average 166.5 days postbaseline.…”
Section: Automated Neuropsychological Assessment Metricsmentioning
confidence: 77%